2005
DOI: 10.1158/0008-5472.can-05-1073
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-Associated Silencing of theNuclear Receptor 1I2Gene in Advanced-Type Neuroblastomas, Identified by Bacterial Artificial Chromosome Array-Based Methylated CpG Island Amplification

Abstract: To identify genes whose expression patterns are altered by methylation of DNA, we established a method for scanning human genomes for methylated DNA sequences, namely bacterial artificial chromosome array-based methylated CpG island amplification (BAMCA). In the course of a program using BAMCA to screen neuroblastoma cell lines for aberrant DNA methylation compared with stage I primary neuroblastoma tumors, we identified CpG methylation-dependent silencing of the nuclear receptor 1I2 (NR1I2) gene. NR1I2 was me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 27 publications
(34 reference statements)
2
71
1
Order By: Relevance
“…To determine whether hypermethylation of CpG sites is associated with transcriptional silencing of the PRTFDC1 gene, we tested the promoter activity of this CpG island in OSCC cells (NA and HSC-2) using a 891-bp fragment (Fragment 1) covering the entire CpG island and 482-bp (Fragment 2) and 409-bp (Fragment 3) fragments covering uncommonly and commonly methylated regions, respectively, in cell lines without expression of PRTFDC1 (Figures 3a and b). We observed a remarkable increase in transcriptional activity of the reporter plasmid containing Fragments 1 and 3 compared with the mock reporter plasmid and reporter plasmid containing Fragment 2 in the plasmidcontaining cell lines (Figure 3b), suggesting that the CpG island around exon 1 of PRTFDC1, especially the region commonly methylated in PRTFDC1-nonexpressing cell lines, contains promoter activity, although few studies, including ours, have shown that promoter activity can be observed in fragments, especially CpG islands, not containing a 5 0 sequence around transcriptional start sites (Kolb 2003;Nakagawachi et al, 2003;Sonoda et al, 2004;Misawa et al, 2005).…”
Section: Identification Of Gene(s) Involved In the Homozygous Deletiomentioning
confidence: 83%
“…To determine whether hypermethylation of CpG sites is associated with transcriptional silencing of the PRTFDC1 gene, we tested the promoter activity of this CpG island in OSCC cells (NA and HSC-2) using a 891-bp fragment (Fragment 1) covering the entire CpG island and 482-bp (Fragment 2) and 409-bp (Fragment 3) fragments covering uncommonly and commonly methylated regions, respectively, in cell lines without expression of PRTFDC1 (Figures 3a and b). We observed a remarkable increase in transcriptional activity of the reporter plasmid containing Fragments 1 and 3 compared with the mock reporter plasmid and reporter plasmid containing Fragment 2 in the plasmidcontaining cell lines (Figure 3b), suggesting that the CpG island around exon 1 of PRTFDC1, especially the region commonly methylated in PRTFDC1-nonexpressing cell lines, contains promoter activity, although few studies, including ours, have shown that promoter activity can be observed in fragments, especially CpG islands, not containing a 5 0 sequence around transcriptional start sites (Kolb 2003;Nakagawachi et al, 2003;Sonoda et al, 2004;Misawa et al, 2005).…”
Section: Identification Of Gene(s) Involved In the Homozygous Deletiomentioning
confidence: 83%
“…BAMCA BAMCA were performed as described elsewhere (Misawa et al, 2005). Test DNA from each of ESCC cell lines was digested first with a methylation-sensitive SmaI and then with methylation-insensitive XmaI.…”
Section: Methodsmentioning
confidence: 99%
“…To identify epigenetic targets in ESCC, we chose an approach using BAMCA for initial screening of ESCC cell lines for aberrantly hypermethylated sequences (Misawa et al, 2005). A summary of our strategy and partial results is provided in Figure 1a and Supplementary Table S1.…”
Section: Methylation Analysis Of Escc Cell Lines By Bamcamentioning
confidence: 99%
“…For colony-formation assays, pCMV-Tag3-RGC32, or the empty vector (pCMVTag3-Mock), was transiently transfected into cells as described elsewhere (Imoto et al, 2003;Misawa et al, 2005). Expression of RGC32 protein in transfected cells was confirmed 48 h after transfection by immunoblotting with anti-Myc antibody (Cell Signaling Technology, Beverly, MA, USA) as described below.…”
Section: Chip Assaymentioning
confidence: 99%